The effects of some engraving and film substrate parameters on the solid density and the dot gain in gravure printing - (:unkn) unknown (SURFACE COATINGS INTERNATIONAL, 2005)
The effects of some engraving and film substrate parameters on the solid density and dot gain in gravure printing were studied by using polyester, BOPP plain film and BOPP co-extruded film substrates. Bi-axially oriented polypropylene (BOPP) is a product utilised in numerous industries such as food packaging, printing, laminating and labeling. It was concluded that the solid density of print is affected by the roughness values of the film substrates. Increasing the roughness value increases the print density. The number of cells per cm(2) and the depth of the cells also affect the solid density. Deeper and fewer cells per cm(2) give a lower solid density value than shallower cells and more cells per cm(2). Engraving parameters have a major effect on the dot gain. The channel between cells has a positive effect on the dot gain. The cell depth and the number of cells per cm(2) also affect the dot gain. The highest dot gain value was measured from the 35% coverage area of all of the scales printed on all the substrates. Also, the highest dot gain values were measured for the prints on polyester the smoothest substrate.
Keywords: gravure; dot gain; solid density; ink; roughness